Characterization and Analysis of Plastic Instability in an Ultrafine‐Grained Medium Mn TRIP Steel. Issue 9 (23rd April 2022) - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay‐Peter; Schaper, Mirko; Zhang, Hanlong; Boller, Christian; Starke, Peter
Abstract : Herein, the mechanical and magnetic behavior of an ultrafine‐grained (UFG) medium manganese (Mn) transformation‐induced plasticity (TRIP) steel is focused on in its plastic instability. The in situ methods of digital image correlation (DIC) and magnetic Barkhausen noise (MBN) are used to macroscopically characterize the propagation of the Lüders band (stretcher–strain marks) and the evolution of MBN activities during quasistatic tensile deformation. The evolution of microstructure during the plastic instability is investigated ex situ using X‐Ray diffraction (XRD) and transmission electron microscopy (TEM) for selected plastic strain states. It is showed in the results that the plastic instability of this steel is associated with an increase of hardness and enrichment of dislocation density, which can also amplify the MBN signal, while the derived coercivity behaves reversely on an overall trend due to work hardening. The different stress response of the medium Mn steel is closely related to the kinetic martensite microstructure, which in turn modifies the domain–structure response. Thus, the MBN can be used as a potential means for nondestructive evaluation (NDE) for the strengthening of the UFG medium Mn TRIP steel. Abstract : Herein, the mechanical and magnetic behaviors of a medium Mn transformation‐induced plasticity (TRIP) in its plastic instability are investigated. The methods of digital image correlation (DIC) and magnetic Barkhausen noise (MBN) are used to characterize the Lüders band propagation during quasistatic tensile deformation. It is showed in the results that the MBN can be used as a potential means for nondestructive evaluation for the strengthening of this steel.